194k views
0 votes
Find the inverse of h(x) = (2x + 6)/5

User Jay Lamont
by
5.2k points

2 Answers

4 votes

Answer:

(5x-6)/2

Explanation:

h(x) = (2x + 6)/5

y = (2x + 6)/5

To find the inverse, exchange x and y

x = (2y+6) /5

Then solve for y

Multiply each side by 5

5x = (2y+6)/5*5

5x = 2y+6

Subtract 6 from each side

5x-6 = 2y+6-6

5x-6 = 2y

Divide by 2

(5x-6)/2 = 2y/2

The inverse is

(5x-6)/2

User Pissall
by
5.7k points
3 votes

Answer:

h^-1(x) = (5x - 6)/2

Explanation:

To find the inverse of h(x) = (2x + 6)/5, we need to solve for 'x':

y = (2x + 6)/5 ⇒ 5y = 2x + 6 ⇒ 5y - 6 = 2x ⇒ x = (5y - 6)/2

Therefore, h^-1(x) = (5x - 6)/2

User Kid
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.